Revised reference values for the intake of protein - Richter, Margrit; Bauer, Jürgen M. (Annals of nutrition & metabolism, 2019)
BACKGROUND: Following a timely update process, the nutrition societies of Germany, Austria, and Switzerland (D-A-CH) revised the reference values for the intake of protein in 2017. The Working Group conducted a structured literature search in PubMed considering newly published papers (2000- 2017). - SUMMARY: For infants < 4 months, the estimated values were set based on the protein intake via breast milk. Reference values for infants > 4 months, children, adolescents, pregnant, and lactating women were calculated using the factorial method considering both requirement for growth and maintenance. For adults, reference values were derived from nitrogen balance studies; for seniors (> 65 years), reports on metabolic and functional parameters under various protein intakes were additionally considered. Reference -values (g protein/kg body weight per day) were set as follows: infants < 4 months: 2.5-1.4, children: 1.3-0.8, adults < 65 years: 0.8, adults > 65 years: 1.0. Key Messages: The reference values for infants, children, adolescents, and adults < 65 years are essentially unchanged compared to recently published values. Scientifically reliable data published between 2000 and 2017 guided the D-A-CH Working Group to set a higher estimated value for adults > 65 years. Since the energy consumption continuously decreases with age, this new estimated protein intake value might be a challenge for the introduction of food-based nutrition concepts for older people.
Gesehen am 14.06.2019